2023
DOI: 10.1080/24740527.2022.2157251
|View full text |Cite
|
Sign up to set email alerts
|

“We survived the pandemic together”: The impact of the COVID-19 pandemic on Canadian families living with chronic pain

Abstract: Introduction Pediatric chronic pain is a significant problem in Canada, affecting one in five youth. This study describes the impact of the pandemic on the experiences of Canadian families living with chronic pain through interviews with youth living with chronic pain, parents, and siblings. Methods Employing a qualitative descriptive design, in-depth semistructured interviews were completed with Canadian youth living with pain, as well as parents and siblings. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…As parents are necessarily involved in pediatric chronic pain treatment, it is an opportune time to provide concurrent support for parents who also have chronic pain. The pandemic revealed the toll of chronic pain on the family system in the absence of usual coping strategies (Killackey et al, 2023). The pandemic also highlighted that it was necessary to support the whole family, as opposed to only youth, in daily pain management with virtual care prioritized to increase accessibility (Birnie et al, 2021).…”
mentioning
confidence: 99%
“…As parents are necessarily involved in pediatric chronic pain treatment, it is an opportune time to provide concurrent support for parents who also have chronic pain. The pandemic revealed the toll of chronic pain on the family system in the absence of usual coping strategies (Killackey et al, 2023). The pandemic also highlighted that it was necessary to support the whole family, as opposed to only youth, in daily pain management with virtual care prioritized to increase accessibility (Birnie et al, 2021).…”
mentioning
confidence: 99%
“…Both parents and siblings reported that the COVID-19 pandemic affected their families in a variety of ways and that restrictions imposed during lock-down impacted coping strategies across the family network. 15 …”
mentioning
confidence: 99%